The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1042/bst20110608
|View full text |Cite
|
Sign up to set email alerts
|

Controlling cancer through the autotaxin–lysophosphatidic acid receptor axis

Abstract: LPA (lysophosphatidic acid, 1-acyl-2-hydroxy-sn-glycero-3-phosphate), is a growth factor-like lipid mediator that regulates many cellular functions, many of which are unique to malignantly transformed cells. The simple chemical structure of LPA and its profound effects in cancer cells has attracted the attention of the cancer therapeutics field and drives the development of therapeutics based on the LPA scaffold. In biological fluids, LPA is generated by ATX (autotaxin), a lysophospholipase D that cleaves the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 48 publications
(50 reference statements)
2
88
0
Order By: Relevance
“…6C) caused a significant reduction in the metastatic nodules in the pretreatment paradigm but did not reach significance in the post-inoculation paradigm (P 5 0.056). Novel Inhibitory Surface in Autotaxin 4-Pentadecyl benzylphosphonic acid, which is also a dual-type inhibitor, caused a significant reduction in the number of metastatic nodules in the lungs (Gupte et al, 2010;Gotoh et al, 2012). Altogether, these findings support the hypothesis that inhibition of the ATX hydrophobic pocket can have similar blocking effects of melanoma metastasis in vivo as inhibiting the ATX active site.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…6C) caused a significant reduction in the metastatic nodules in the pretreatment paradigm but did not reach significance in the post-inoculation paradigm (P 5 0.056). Novel Inhibitory Surface in Autotaxin 4-Pentadecyl benzylphosphonic acid, which is also a dual-type inhibitor, caused a significant reduction in the number of metastatic nodules in the lungs (Gupte et al, 2010;Gotoh et al, 2012). Altogether, these findings support the hypothesis that inhibition of the ATX hydrophobic pocket can have similar blocking effects of melanoma metastasis in vivo as inhibiting the ATX active site.…”
Section: Resultssupporting
confidence: 75%
“…After injection into C57BL/6 mice via the tail vein, the syngeneic B16-F10 melanoma cells metastasize primarily to the lungs in an ATX-dependent manner (Baker et al, 2006;Gupte et al, 2011;Gotoh et al, 2012). We showed that in this model administration of an ATX inhibitor up to 48 hours postinoculation of the melanoma cells still causes a significant reduction in the number of metastatic lung nodules, indicating a role for ATX in the colonization and seeding of the lungs with melanoma cells (Gotoh et al, 2012). We tested compounds 1 and 3 by treating mice 1 day prior or 1 day after inoculation of B16-F10 melanoma cells via the tail vein, and continued for an additional 10 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial relation of ATX/LPA signaling with melanoma cells resulted in much of the early research into ATX being concentrated in the cancer field [39,[57][58][59][60][61][62][63][64][65] . LPA increases vascular endothelial growth factor (VEGF) production, which stimulates angiogenesis [66] , a process necessary for tumor progression.…”
Section: Overview Of the Atx-lpa-lpp Axis Atx -The Predominant Producmentioning
confidence: 99%
“…Finally, it is well known that LPA signalling inuences cancer-related processes, 63 especially via LPA 2 . Nevertheless, there is also evidence of LPA 1 implication in cancer progression, specically in ovarian, breast and gastrointestinal ones.…”
mentioning
confidence: 99%